2014
DOI: 10.1007/s11207-014-0486-x
|View full text |Cite
|
Sign up to set email alerts
|

Are There Different Populations of Flux Ropes in the Solar Wind?

Abstract: Flux ropes are twisted magnetic structures, which can be detected by in-situ measurements in the solar wind. However, different properties of detected flux ropes suggest different types of flux-rope population. As such, are there different populations of flux ropes? The answer is positive, and is the result of the analysis of four lists of flux ropes, including magnetic clouds (MCs), observed at 1 AU. The in-situ data for the four lists have been fitted with the same cylindrical force-free model, which provide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 66 publications
(107 reference statements)
3
56
0
Order By: Relevance
“…Therefore, Feng et al [] proposed that SIMFRs originate from the Sun and are interplanetary manifestations of small coronal mass ejections (CMEs). In addition, some authors discussed the origin of SIMFRs by investigating the possible relationship between SIMFRs and MCs and found that SIMFRs and MCs have many common and similar (or relative) characteristics [e.g., Feng et al , , , ; Cartwright and Moldwin, ; Feng and Wu, ; Yu et al , ; Janvier et al , , ; Feng and Wang, ]. These authors tend to agree with the view that SIMFRs originate from solar corona.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, Feng et al [] proposed that SIMFRs originate from the Sun and are interplanetary manifestations of small coronal mass ejections (CMEs). In addition, some authors discussed the origin of SIMFRs by investigating the possible relationship between SIMFRs and MCs and found that SIMFRs and MCs have many common and similar (or relative) characteristics [e.g., Feng et al , , , ; Cartwright and Moldwin, ; Feng and Wu, ; Yu et al , ; Janvier et al , , ; Feng and Wang, ]. These authors tend to agree with the view that SIMFRs originate from solar corona.…”
Section: Introductionmentioning
confidence: 92%
“…Coronagraph and in-situ observations revealed that coronal jets can produce signatures in the outer corona, sometimes even at Earth or beyond (St. Cyr et al 1997;Wang et al 1998;Wood et al 1999;Corti et al 2007;Neugebauer 2012;Janvier et al 2014;Yu et al 2014). It was therefore suggested that they contribute to powering the corona and solar wind (e.g., Shibata et al 2007;Cirtain et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…MCs are of great interest due to their associations with strong solar eruptions and potentially immense geoeffectiveness (e.g., H. Hu et al, ; Wang, Zhang, et al, ). SFRs contribute mainly to slow solar wind, and their source regions and formation mechanisms are still under discussion (e.g., Feng et al, , ; Janvier et al, , ; Kilpua et al, ; Tian et al, ; Yu et al, , ; Zheng & Hu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Different from MCs that originate from the solar corona, SFRs are believed to have two source regions: the solar corona and the interplanetary medium (e.g., Cartwright & Moldwin, ; Feng et al, ; Janvier et al, ; Moldwin et al, ; Rouillard et al, ; Tian et al, ; Yu et al, , ). SFRs originating in the solar corona can be classified into two categories.…”
Section: Introductionmentioning
confidence: 99%